Is the Inhibition of Dipeptidyl Peptidase-4 (DDP-4) Enzyme Route Dependent and/or Driven by High Peak Concentration?– Seeking Answers with ZYDPLA1, a Novel Long Acting DPP-4 Inhibitor, in a Rodent Model - Patel, Harilal; Joharapurkar, Amit A.; Bahekar, Rajesh; Patel, Prakash; Kshirsagar, Samadhan G.; Modi, Nirav; Ghoghari, Ashok; Patel, Vishal J.; Jain, Mukul R.; Srinivas, Nuggehally R.; Patel, Pankaj R.; Desai, Ranjit C. (Drug Research, 2017)
ZYDPLA1 is a long acting enzyme dipeptidyl peptidase-4 (DPP-4) inhibitor. The comparative effect of DPP-4 inhibition after intravenous (IV) and oral administration of ZYDPLA1 in a rat model was evaluated to answer the question of route dependency and/or the need of high plasma levels of ZYDPLA1. The study was conducted using parallel design in male Wistar rats for IV/oral route (n=9 and 6, for IV and oral respectively). A single 30 mg/kg dose of ZYDPLA1 was administered. Plasma samples were analysed for ZYDPLA1 concentration and DPP-4 inhibition. Pharmacokinetic analysis was carried out to assess peak concentration, area under the concentration–time curve, total body clearance, elimination half-life, and mean residence time. The PK/PD correlation was performed using standard sigmoidal Emax modelling to derive; maximum effect (Emax) and concentration to exert 50% Emax effect (EC50). ZYDPLA1 showed rapid absorption, high volume of distribution, low clearance, and complete oral bioavailability. The Emax derived after both routes and corresponding PK/PD profile showed comparable DDP-4 inhibition. The EC50 for IV (0.021 µg/mL) was comparable to the oral route (0.019 µg/mL). ZYDPLA1 showed full DPP-4 inhibition without regard to the route of administration. Higher systemic peak levels showed no bearing on the DDP-4 inhibition.
Keywords: ZYDPLA1; DPP-4; Type 2 diabetes mellitus; high performance liquid chromatography tandem mass spectrometry; pharmacokinetics; pharmacodynamics; plasma